Intellectual Capital and Its Impact on Achieving Competitive Advantages for Businesses: A Survey Study of The General Company for Ready-Made Garments in Mosul - ALabass, Hasan S.; M. Abdulnabi, Shuaib (PROSPECTIVE RESEARCHES, 2026)
The study dealt with restricting the extant of intellectual impact in achieving the competitive characteristics in the commercial organizations. The study demonstrated a theoretical frame for the most recent knowledge that the researchers presented concerning the two dimensions of the current study. The first dimension was represented in the intellectual capital which is considered one of the most recent subjects in contemporary administration, and the most important constituent of the national wealth and the most expensive asset of the companies assets especially that is connected to knowledge and experience which are existed in the minds of individuals and can be used appropriately for the sake of creating wealth. The intellectual capital consists of three constituents and they are: human resource, infrastructure, and customers. The second dimension represented the competitive characteristics which the organizations are trying to owe weather those organizations are industrial, services, governmental or commercial organizations related to the private sector, and how to maintain those characteristics staying in the best position; i.e. continuance of gaining competitive characteristics through following up what is happening as changes in the environment and practical marketing developments. This means enhancing the categories of competitive priorities in terms of cost, quality, flexibility, time of delivery, distinction and creativity. When an organization owned the most valuable assets, the intellectual-scientific-epistemological assets, represented in the intellectual capital which is capable of rapid adaptation to the environmental changes, the matter which will let this organization to have a competitive characteristic provided by these assets. Because of the narrow range of such relation between these two dimension; the researcher sought for including these two dimension with their varieties within a comprehensive frame to study the relation between them.